The food and health environment in junior secondary schools in urban Burkina Faso: a cross-sectional study of administrators, food vendors and early adolescents - Mauti, Joy; Mank, Isabel; De Neve, Jan-Walter; Gyengani, Guillaume Alfred; Somé, Paul-André; Shinde, Sachin; Fawzi, Wafaie; Bärnighausen, Till; Vandormael, Alain (International journal of environmental research and public health, 2021)
School enrolment rates have increased globally, making the school environment a unique setting to promote healthy nutrition and eating outcomes among early adolescents. In this cross-sectional study, we describe the food and health environment of junior secondary schools in Ouagadougou (Burkina Faso, West Africa). We evaluated the food and health environment using three components: (1) the implementation of health-related policies or guidelines in the schools, (2) the provision of health, nutrition and water, sanitation & hygiene (WASH) services in the schools, and (3) the quality of the school food environment, including foods sold by vendors. We used stratified random sampling to recruit 22 junior secondary schools from the five Ouagadougou districts in 2020. Trained fieldworkers collected standardized questionnaire data from 19 school administrators, 18 food vendors, and 1059 in-school adolescents. We report that only 7 out of 19 school administrators were aware of existing health-related policies and guidelines at their school and only 3 schools had a school health and nutrition curriculum in place. The overall provision of health, nutrition and WASH services was low or inadequate. Likely because of the lack of school canteens, 69% of the students bought snacks and unhealthy foods from food vendors. There is a critical need to improve the food and health environment of junior secondary schools in urban Burkina Faso.
Gesehen am 02.12.2021